Legal Protection for Consumers Who Use Thematic Cosmetics in Indonesia - Natanael Pakpahan; Kartina Pakpahan; Ayu Priska Nibenia Zega; Ester Affia Sifra Manalu; Ridho Gokasi Paulus Tampubolon (Warmadewa Press, 2024)
Thematic Cosmetics are traditional cosmetics made from natural ingredients and are identical to a region and are in demand by the community. Due to this development, some communities try to make and sell thematic cosmetics without paying attention to BPOM permits. Therefore, this study aims to determine the legal protection for consumers who use thematic cosmetics, to find out the systematic registration of thematic cosmetics to obtain BPOM permits, and to find out the supervision of thematic cosmetics that applies in Indonesia. This study uses the Normative Juridical method, this literature study is a series of activities related to the stages of collecting literature data, understanding then recording, and processing research materials. Each province in Indonesia has a Food and Drug Supervisory Agency which is tasked with supervision, law enforcement, and guidance, BPOM supervises the quality of cosmetics starting from the registration and assessment stages, with the latest regulation, namely BPOM Regulation No. 21 of 2022 concerning Procedures for Submitting Cosmetic Notifications replacing Regulation No. 12 of 2020 which is considered no longer appropriate. The Food and Drug Supervisory Agency has the authority to supervise the circulation of each productan d destruction of products that do not meet the requirements. Create standards and requirements related to product quality, safety, and benefits as well as inspection of production and distribution facilities and technical guidelines for laboratory assessment and testing.